2021
DOI: 10.1002/jpen.2204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a targeted volume‐increase nutrition guideline on growth and body mass index in premature infants: A retrospective review

Abstract: Background:The negative impact of disproportionate growth in premature infants is well documented, but optimal nutrition practices needed to prevent an unhealthy body mass index (BMI) remain unclear.Methods: An evidence-based, volume-increase guideline that advanced feeding volumes from 150-160 to 170-180 ml/kg/day between the postmenstrual age (PMA) of 31 0/7 and 34 0/7 weeks was implemented in October 2017 for infants born at ≤32 0/7 weeks' gestational age. Data were collected on 262 infants' weight and leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These procedures may partially account for differences in feeding strategy between the two groups; however, the two groups were strictly matched with the BW, GA, and PMA in the same NICU. According to the nutritional guidelines, 43 the feeding volume of infant (similar PMA and weight) feeding strategy and feeding volume. In the present study, the amounts of daily feeding and weights on the day of the blood draw were comparable between the ROP group and the non-ROP group ( P = 0.524 and P = 0.140, respectively) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…These procedures may partially account for differences in feeding strategy between the two groups; however, the two groups were strictly matched with the BW, GA, and PMA in the same NICU. According to the nutritional guidelines, 43 the feeding volume of infant (similar PMA and weight) feeding strategy and feeding volume. In the present study, the amounts of daily feeding and weights on the day of the blood draw were comparable between the ROP group and the non-ROP group ( P = 0.524 and P = 0.140, respectively) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, providing >2.5 gr/kg of protein was associated with improved head growth, and non‐survivors received less protein than surviving infants 27 . The use of higher feeding volumes (170–180 vs. 150–160 ml/kg/d) significantly reduced disproportionally low body mass index (BMI) in 262 preterm infants born earlier then 32 weeks’ gestation 28 . Moreover, new therapeutic approaches such as combining relevant hormones may be considered facing the impact of birth at early gestational age and the insufficiency of optimal nutrition to their growth 29 .…”
Section: Discussionmentioning
confidence: 99%
“…150-160 ml/kg/d) significantly reduced disproportionally low body mass index (BMI) in 262 preterm infants born earlier then 32 weeks' gestation. 28 Moreover, new therapeutic approaches such as combining relevant hormones may be considered facing the impact of birth at early gestational age and the insufficiency of optimal nutrition to their growth. 29 These new practices emphasise the need for a conceptual change in planning nutrition for VLBW infants with morbidities, directed towards individualised care, and based on morbidity and growth parameters that are currently not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent scientific research has demonstrated that optimizing the nutrition of premature infants between 31 and 34 weeks of corrected gestational age can have a positive impact on their body mass index (BMI) proportionality at the time of their discharge from hospital [23]. According to a recent study, providing the optimal nutrition to infants during their initial months is crucial for their healthy development.…”
Section: Discussionmentioning
confidence: 99%